Environmental cues rather than quality of supplemented pollen drive the foraging behaviour of honey bees during avocado pollination - Madlen Kratz; Robert Manning; Lynne Milne; Kenneth Dods; Boris Baer; Dominique Blache (Scientific Reports)
Abstract Honey bee colonies adapt their foraging behaviours to the availability of floral resources to meet their nutritional needs. However, it is unknown if the nutritional quality of stored or supplemented pollen can influence the floral choices of bees during commercial crop pollination. The foraging behaviour of bees from 40 colonies was studied during avocado pollination in southern Western Australia. A pollen database of the orchard was built and used to assess the floral preference of the bees. Pollen collectors and nectar foragers showed different foraging behaviour as indicated by their Dominance Candidate Index (DCI). The foraging choices were partially affected by the type of supplemented pollen that consisted of agricultural and forest species. Aside from nutritional cues, floral source abundance and attractiveness played a role in influencing the foraging behaviour for pollen and nectar. Both pollen and nectar foragers chose a sub-set of flowers available at the avocado orchard. Foraging bees respond strongly to various environmental cues that potentially underlie energetic investment and food reward principals.